2019
DOI: 10.1183/13993003.02066-2018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the MILES cohort reveals determinants of disease progression and treatment response in lymphangioleiomyomatosis

Abstract: IntroductionThe Multicenter International Lymphangioleiomyomatosis (LAM) Efficacy of Sirolimus (MILES) trial revealed that sirolimus stabilised lung function in patients with moderately severe LAM. The purpose of this study was to further examine the MILES cohort for the effects of racial, demographic, clinical and physiological patient characteristics on disease progression and treatment response in LAM.MethodsMILES subjects were stratified on the basis of menopausal status (pre-menopausal/post-menopausal), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
1
36
0
6
Order By: Relevance
“…Mladší, premenopauzální ženy mají obvykle rychlejší pokles plicních funkčních parametrů nežli ženy starší, postmenopauzální [6,7]. Předpokládá se, že pacienti s TS/ LAM mají ve srovnání se S/ LAM mírnější a méně progresivní onemocnění [52,53]. V našem souboru máme jen dvě pacientky s TS/ LAM.…”
Section: Schéma 1 Signalizační Dráha Mtor a Působení Inhibitoru Mtorunclassified
“…Mladší, premenopauzální ženy mají obvykle rychlejší pokles plicních funkčních parametrů nežli ženy starší, postmenopauzální [6,7]. Předpokládá se, že pacienti s TS/ LAM mají ve srovnání se S/ LAM mírnější a méně progresivní onemocnění [52,53]. V našem souboru máme jen dvě pacientky s TS/ LAM.…”
Section: Schéma 1 Signalizační Dráha Mtor a Působení Inhibitoru Mtorunclassified
“…LAM is usually diagnosed in women of reproductive-age, suggesting an important role for female sex hormones in disease pathogenesis . Clinical observations that the menstrual cycle influences respiratory symptoms and occurrence of pneumothorax, and that decline of lung function slows after menopause and accelerates with exogenous estrogen use and pregnancy are consistent with this concept (Cohen et al, 2009;Gupta et al, 2019;Johnson and Tattersfield, 1999;Shen et al, 1987). Lymphadenopathy caused by LAM is more prominent in the pelvis and retroperitoneum than in the nodes in upper abdomen, thorax and mediastinum, suggesting a pelvic source for the neoplasm (Glasgow et al, 2008;Tobino et al, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…The allele frequency of TSC1 or TSC2 mutations within LAM lesions range from 4% to 60%, with average less than 20% (Badri et al, 2013), supporting the concept that recruited stromal cells, rather than mutation-bearing LAM cells, dominate within the lesions (Badri et al, 2013;Clements et al, 2015;Johnson and Tattersfield, 1999). The mTOR inhibitor, Sirolimus, is an FDA-approved suppressive therapy that stabilizes lung function in most LAM patients (Gupta et al, 2019;McCormack et al, 2011); however, the drug does not eliminate LAM cells and can be associated with significant side-effects (McCormack et al, 2011). There is therefore an urgent need to develop new molecular targets and treatments for LAM.…”
Section: Introductionmentioning
confidence: 99%
“…Skin lesions include hypomelanotic macules (90% of patients), facial angiofibromas (75% of patients), fibrous cephalic plaques (25% of patients) and shagreen patches (> 50% of patients) (1). Study has reported that the use of sirolimus on specific TSC manifestations (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%